Risk Evaluation Approach and Application Research on Fuzzy-FMECA Method Based on Cloud Model - Zhengjie Xu; Youpeng Zhang; Hongsheng Su (Institute of Advanced Engineering and Science, 2014)
In order to safeguard the safety of passengers and reducemaintenance costs, it is necessary to analyze and evaluate the security risk ofthe Railway Signal System. However, the conventional Fuzzy Analytical HierarchyProcess (FAHP) can not describe the fuzziness and randomness of the judgment,accurately, and once the fuzzy sets are described using subjection degreefunction, the concept of fuzziness will be no longer fuzzy. Thus Fuzzy-FMECAmethod based on cloud model is put forward. Failure Modes Effects andCriticality Analysis (FMECA) method is used to identify the risk and FAHP basedon cloud model is used for determining the subjection degree function in fuzzymethod, finally the group decision can be gained with the syntheticallyaggregated cloud model, the method’s feasibility and effectiveness are shown inthe practical examples. Finally Fuzzy-FMECA based on cloud model and theconventional FAHP are used to assess the risk respectively, evaluation resultsshow that the cloud model which is introduced into the risk assessment ofRailway Signal System can realize the transition between precise value andquality value by combining the fuzziness and randomness and provide moreabundant information than subjection degree function of the conventional FAHP. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3886